Club House Hotel viewed from across the street, Yass, New South Wales, ca. 1970 - Stacey, Wes (Wesley), 1941-2023. (1968)
Depicting two storey corner verandah, cast-iron balustrade, valence, roofline, hotel sign.
Part of the Wes Stacey archive of architectural photographs, 1968-1972.
Catalogue record generated as part of a batch load.
Title from acquisitions document, see file NLA09/703.
Wes Stacey reference number: 5 19 8.
Also available online
Keywords: Hotels -- New South Wales -- Yass -- Photographs; Verandas -- New South Wales -- Yass -- Photographs; Decorative cast-ironwork -- New South Wales -- Yass -- Photographs; Metal roofing -- New South Wales -- Yass -- Photographs; Yass (N.S.W.) -- Buildings, structures, etc. -- Photographs